Meningkatkan Aktivitas dan Hasil Belajar Bahasa Indonesia dengan Penerapan Model Pembelajaran Examples non Examples - Maraatussoaliha Maraatussoaliha (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to improve the activities and learning outcomes of Indonesian language writing materials for students of class XII IPA 6 MAN 2 Kota Bima through the example non example learning model. The subjects of this study were students of class XII IPA 6 MAN 2 Kota Bima. The data were analyzed using qualitative descriptive techniques by presenting original data in the form of field notes, observation sheets, assessment sheets for writing editorial texts, and photos of activities. The results of the research obtained are learning to write editorial texts has increased significantly. Before being subjected to action, students are still not active during learning activities. After being subjected to action, students become active during the teaching and learning process. As for the learning outcomes, the first cycle of student learning outcomes was 90.6% and in the second cycle the completeness reached 100%. Product skills have also improved. Before being subjected to action, the average value of the class was 48.3%, in the first cycle it was 59.4% and in the second cycle it increased to 81.3%. In conclusion, the application of the example non-example learning model can improve activities and learning outcomes of Indonesian language writing materials for editorial texts for class XII IPA 6 MAN 2 Kota Bima in the odd semester of the 2019/2020 school year. Keywords: Activity, Non Example, Learning Outcomes